Русский след» в истории сербской литературы и критики 20-30-х гг. ХХ века (к вопросу о роли русской эмиграции в культурной жизни Сербии) (Filološke studije, 2019)
The paper deals with the life of the Russian diaspora in Yugoslavia in 20-30th ХХ century and with the influence of the Russian emigration on a cultural life of Serbia.